(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
In a benthic macrofaunal survey of the continental shelf of northern Chile a peculiar filamentous material was collected in grab and dredge samples of greenish, foul smelling sediment from depths of 50 to 280 m (ref. 1). In reporting the results emphasis was placed, however, on the fact that a virtually iazoic* bottom had beenfound between depths of 50 to 400 m. Average biomass was only 0.17 g (wet weight) /m2 , with 6.6 individuals /m2*. The distribution of the azoic sediments coincided with low oxygen concentrations in the water above (ref. 2). The author again found white filamentous material while sampling the benthos off the Bay of Concepcion and the Gulf of Arauco, in central Chile. These findings together with the casual observation of filaments in the mouth parts of the commercially important galatheid shrimp Pleuroncodes mondon, initiated new efforts to learn about this material and its possible ecological significance.